PERSEPSI MASYARAKAT TERHADAP PETERNAKAN AYAM PETELUR DI DESA AMPELGADING KELURAHAN SELOREJO KABUPATEN BLITAR: PERSEPSI MASYARAKAT TERHADAP PETERNAKAN AYAM PETELUR DI DESA AMPELGADING KELURAHAN SELOREJO KABUPATEN BLITAR - indah, lilik (Program Studi Peternakan, 2026)
This study aims to determine public perceptions of the existence of laying hen farms in Ampelgading Village, Selorejo District, Blitar Regency. Laying hen farms contribute to the economy through the provision of eggs, employment, and manure, but also cause negative impacts such as odor, soil pollution, and an increase in fly populations. This study used a quantitative descriptive method with a survey technique of 34 respondents selected using the Slovin formula. Data were collected through observation, interviews, questionnaires, and literature studies, and analyzed using a Likert scale. The results showed that positive public perceptions included the benefits of the availability of eggs (94 points), manure (68 points), and job opportunities (62 points), with a total score of 75 (category quite beneficial), while negative public perceptions were indicated by disturbances caused by flies (89 points), odor (80 points), and soil pollution (80 points), with a total score of 83 (category very disturbing). Despite providing economic benefits, laying hen farms also cause public unrest regarding environmental impacts, so better waste management is needed to maintain community comfort and the sustainability of livestock businesses.